PHYSIOTHERAPY INTERVENTION IN PNEUMONY PATIENTS IN DUNGUS LUNG HOSPITALS - Suryawiningrum, Widya; Wijianto, W; Setiawan, Agus (Universitas Muhammadiyah Surakarta, 2021)
Pneumonia is caused by an infection that occurs in the air sacs caused by viruses, bacteria to fungi, attacking one or both lungs, which results in the alveoli being filled with fluid or pus, making it difficult for the patient to breathe. Pneumonia is the most common cause of death in the world with nearly 3.5 million deaths per year (Wunderink RG, Waterver GW., 2014). According to the incidence of infection with pneumonia, pneumonia is divided into two. Community pneumonia if the patient is infected from the community and nosocomial pneumonia if the patient is infected in the hospital. The goal to be achieved is to find out the benefits of providing physiotherapy interventions in the form of Chest Physiotherapy in reducing patient complaints in Pneumonia conditions at Dungus Lung Hospital. The results obtained after 3 times of therapy showed that shortness of breath decreased from a value of 5 (severe shortness of breath) to a value of 4 (somewhat severe).